2016
DOI: 10.1002/ece3.2571
|View full text |Cite
|
Sign up to set email alerts
|

Cancer brings forward oviposition in the fly Drosophila melanogaster

Abstract: Hosts often accelerate their reproductive effort in response to a parasitic infection, especially when their chances of future reproduction decrease with time from the onset of the infection. Because malignancies usually reduce survival, and hence potentially the fitness, it is expected that hosts with early cancer could have evolved to adjust their life‐history traits to maximize their immediate reproductive effort. Despite the potential importance of these plastic responses, little attention has been devoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…genetic, epigenetic, adaptive phenotypic plasticity…) are under strong selection each time a novel malignancy occurs. Each primary tumor originates from a single cell that has to “reinvent the wheel” given that its evolved, malignant, products die with the host , but see the case of transmissible cancers . The highly sophisticated level of organization that coalescent cancer cells achieve in few months or years in tumors within an individual, and laterally between individuals and across species, would be an illustration of convergent evolution – somatic selection operating in environments that are broadly governed by the same ecological constraints (i.e.…”
Section: The Somatic Selection Modelmentioning
confidence: 99%
“…genetic, epigenetic, adaptive phenotypic plasticity…) are under strong selection each time a novel malignancy occurs. Each primary tumor originates from a single cell that has to “reinvent the wheel” given that its evolved, malignant, products die with the host , but see the case of transmissible cancers . The highly sophisticated level of organization that coalescent cancer cells achieve in few months or years in tumors within an individual, and laterally between individuals and across species, would be an illustration of convergent evolution – somatic selection operating in environments that are broadly governed by the same ecological constraints (i.e.…”
Section: The Somatic Selection Modelmentioning
confidence: 99%
“…While, at this stage, tumors are not found to affect the survival of flies, previous research suggests that cancer may affect fitness in other ways. Female Drosophila, bearing colorectal tumors, bring forward their peak oviposition period suggesting that flies are adapted to minimize the costs of cancer on fitness (18). The social behavior of cancerous flies found in this study could also be interpreted as an adaptive process, which reduces cancer progression.…”
Section: Discussionmentioning
confidence: 59%
“…In Drosophila, social isolation leads to a reduced lifespan (23), increased aggression (24)(25)(26), reduced need for sleep (27, 28) and a decrease in the fiber number of the mushroom bodies in the integrative nervous center (29). Furthermore, tumor-like over-proliferation of tissues has been found to occur naturally in Drosophila (30, 31) and induced tumors have also been found to influence fitness traits in individuals (16,18) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemic neoplasia in blue mussels ( Mytilus trossulus ) causes reduced phagocytic capacity of haemocytes, leading to reduced immune function and ultimately to increased mortality . Moreover, laboratory experiments showed that Drosophila females with cancer oviposit earlier than healthy ones . The emergence and spread of a transmissible cancer, devil facial tumour disease (DFTD), within Tasmanian devil populations, provides an ideal model system to monitor the long‐term impact of cancer on devil fitness, and to investigate host responses in the evolutionary arms‐race of malignant cells and their hosts.…”
Section: Introductionmentioning
confidence: 99%